Judicial Jurisdiction for Electronic Administrative Contracts in Jordanian Legal System (Contrastive Study) (International Journal of Psychosocial Rehabilitation, 2020)
The importance of this study is to clear the distinctive elements of electronic administrative contracts, and it tries to distinguish between electronic administrative contracts and civil or private contracts so it can clarify the appropriate court, ordinary or administrative, and which legislation or law should be used upon these types of contracts, as we are using a special law for those electronic administrative contracts. Also, this study tried to find the general confined to a legal part of the liquidation of damages rather than the power of cancellation. To get the results we are looking for, we tried the comparative study between Jordanian legislation and some other countries. This study ends with some conclusions and results, such as there are differences between electronic contracts and civil ones, which means legislators should make new legislation for administrative contracts. Also, we recommend making special courts for administrative contracts.